PEMBELAJARAN KITAB TA’LIM MUTA’ALLIM TERHADAP PERILAKU SANTRI - Edo Suwandi, Oking Setia Priyatna, H. Kamalludin (LP2M Universitas Muslim Nusantara Al Washliyah, 2020)
Ta'lim Al Muta'allim was a well-known work of Shaykh Al-Zarnuji, which contains the full attitude of the disciples ' obedience to the teachers. This work is one of the main pillar of Islamic Boarding School education. Learning activities about the book are expected to improve the behavior of students, especially when studying. Therefore, the author is interested to examine the influence of the study of the Book of Ta'lim Muta'alim on the behavior of students at the Pondok Pesantren Nurul Hidayah Jasinga. This research aims to determine the influence of the study of the Book of Ta'lim Muta'alim on the behavior of students at the Pondok Pesantren Nurul Hidayah Jasinga. This study was conducted using quantitative approaches and correlational methods. The data collection technique used is questionnaire. Then the analysis of the data used is the correlation analysis technique Product Moment. Based on the results of analysis of data conducted, obtained a rcount value of 0.652. In a simple interpretation the figure is in the 0.40-0,70 range which means between the X and Y variables there is a moderate or sufficient correlation. Then by using a significance table of 5% obtained rtable amounting to 0.334 from 33 samples. So it can be concluded that Ho or the null hypothesis is rejected and Ha is accepted due to rcount 0.652 > rtable 0.334. This means that there is a relationship between Ta'lim Muta'alim Learning and students ' behavior in the Pondok Pesantren Nurul Hidayah Jasinga.